(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This paper explores strategies to enhance student engagement and retention in higher education institutions in Cameroon, focusing on interactive and collaborative learning tools. The study examines current practices, challenges, and the potential benefits of integrating innovative learning methods to foster an engaging educational environment. Using a mixed-methods approach, integrating both qualitative and quantitative data, this research identifies key factors influencing student engagement and retention. Surveys and interviews conducted with students, educators, and administrators provide comprehensive insights into the effectiveness of these learning tools. The findings highlight the positive impact of interactive platforms and collaborative activities on student motivation and academic success. Furthermore, the paper discusses the challenges faced in implementing these strategies, such as limited access to technology and inadequate training for educators. By addressing these issues, the study offers actionable recommendations for educators, policymakers, and stakeholders in the Cameroonian higher education sector to improve student outcomes and create a more supportive learning environment.